Drug-induced lupus in anti-TNF-alpha therapy and its treatment with rituximab (2012)
We report three patients with rheumatoid arthritis (RA) who were treated with anti-TNF-α agents and who developed drug-induced lupus (DIL). Two of them received etanercept and the remainder adalimumab. We also present the favorable response observed with the withdrawal of the anti-TNF-alpha agents and the introduction of rituximab. Through this intervention, we observed a very good control of the activity of both DIL and RA without additional adverse reactions.